Histone Deacetylase Inhibition in Non-small Cell Lung Cancer: Hype or Hope? - Mamdani, Hirva; Jalal, Shadia I. (Frontiers in Cell and Developmental Biology, 2020)
Epigenetic modulation, including acetylation, methylation, phosphorylation, and ubiquitination, plays a pivotal role in regulation of gene expression. Histone acetylation -a balance between the activities of histone acetyltransferases (HATs) and histone deacetylases (HDACs) -is one of the key epigenetic events. Our understanding of the role of HDACs in cancer is evolving. A number of HDAC isoenzymes are overexpressed in a variety of malignancies. Aberrant histone acetylation is associated with dysregulation of tumor suppressor genes leading to development of several solid tumors and hematologic malignancies. Pre-clinical studies have demonstrated that HDAC-1 gene expression is associated with lung cancer progression. Histone hypoacetylation is associated with more aggressive phenotype in adenocarcinoma of the lung. HDAC inhibitors (HDACi) have pleiotropic cellular effects and induce the expression of pro-apoptotic genes/proteins, cause cellular differentiation and/or cell cycle arrest, inhibit angiogenesis, and inhibit transition to a mesenchymal phenotype. Consequently, treatment with HDACi has shown anti-proliferative activity in non-small cell lung cancer(NSCLC) cell lines. Despite promising results in pre-clinical studies, HDACi have shown only modest single agent activity in lung cancer clinical trials. HDAC activation has been implicated as one of the mechanisms causing resistance to chemotherapy, molecularly targeted therapy, and immune checkpoint inhibition. Therefore, there is a growing interest in combining HDACi with these agents to enhance their efficacy or reverse resistance. In this paper, we review the available preclinical and clinical evidence for the use of HDACi in NSCLC. We also review the challenges precluding widespread clinical utility of HDACi as a cancer therapy and future directions.